"How far do you have to walk to find peace again?": A case study of First Nations' operational values for a community forest in Northeast British Columbia, Canada. (24th March 2013) - Booth, Annie L.; Muir, Bruce R.
Abstract: In this paper we report upon research conducted with two First Nations located in British Columbia, Canada (Saulteau First Nations and West Moberly First Nations) on their preferences regarding forest operations within their community forest license. We confirmed the forestry‐related values previously documented in other research, and we are able to determine specific parameters with regard to the protection or integration of these values, particularly those that are ecologically based. In addition, we identify significant cultural values expected in forestry planning and management, their parameters, as well as values not commonly discussed within the literature, such as concerns over non‐indigenous access and conflicting, overlapping resource tenures. We conclude that further research, which accounts for and readily accommodates indigenous values and preferences, is needed to examine North American indigenous participation in both community forest tenures and in developing forest operation planning.